2020
DOI: 10.1155/2020/5281957
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Patterns of Skin Disease in Saudi Arabia: A Systematic Review and Meta-Analysis

Abstract: Background. Large epidemiological studies on patterns of skin diseases in Saudi Arabia are scarce. Therefore, this systematic review and meta-analysis was conducted to gather available epidemiologic data describing the pattern of skin diseases in different geographical areas in Saudi Arabia. Methods. A comprehensive literature search of articles was conducted in PubMed, SCOPUS, and Web of Science through October 2019. We included all published cross-sectional studies that provided data on relevant incidence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Smoking rates in men (19.8%) and women (2.6%) were concordant with the national statistics. 14 Similarly, the past history of eczema (25%) and asthma (17%) in our study was in line with the previously reported prevalence of eczema 15 and asthma 16 in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 90%
“…Smoking rates in men (19.8%) and women (2.6%) were concordant with the national statistics. 14 Similarly, the past history of eczema (25%) and asthma (17%) in our study was in line with the previously reported prevalence of eczema 15 and asthma 16 in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 90%
“…25 A recent systematic review and meta-analysis demonstrated the pattern of skin disorders in a total of 30,436 patients of different geographical locations of Saudi Arabia (Almohideb, 2020) and reported skin appendages (24.8%) and dermatitis (24.0%) as the most often reported skin disorders in Saudi Arabia. 26 Skin infection accounted for 18.5%, whereas papulosquamous disorders accounted for 5.3%. Psoriasis accounted for 3.9%, whereas lichen planus accounted for 1.8%.…”
Section: Dovepressmentioning
confidence: 99%
“…Almohideb 2020 26 Riyadh Meta-analysis of 30,436 patients with skin diseases from different regions of the KSA; the prevalence of psoriasis among these patents was 3.9% more in males. Almutairi et al 2020 40…”
Section: Albarraq Et Almentioning
confidence: 99%
“…It was noted that 7.5% of the conditions were related to hair loss and the proportion of subjects identified with hair loss was higher among females, which is similar to our findings; however, specific types of alopecia and its determinants were not indicated in the review. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%